Detection the Role of Coxiella burnetii in Abortion of Women in the Thi - Qar Province-Iraq. - Jaber, Mohamed A.; Hindi, Abdalah, K.; Mutar, Abbas, D. (University of Thi-Qar Journal, 2019)
Coxiella burnetii bacteria, an obligate intracellular with a worldwide geographical distribution, are the causative agent of Q fever in humans. In this study a total of 40 serum samples collected from aborted women in Bent Al Huda hospital in southern of Iraq. By enzyme linked immunosorbent assay (ELISA) targeting immunoglobulin G antibody (IgG) of this bacterium in serum samples. The C. burnetii diagnosed in 8 (20 %) in clinical samples and 6 (15%) samples were equivocal to IgG antibody. And the frequent diagnose of immunoglobulin association of the pathogen with cases of spontaneous abortion. These first studies on this bacterium which remain not diagnose as causative agents of abortion and that the prevalence in Iraq is non-studied. The present study demonstrated the high prevalence of Coxiella burnetii in aborted woman. Therefore, Q fever could be responsible for considerable numbers of woman abortions in Iraq.